2010
DOI: 10.1186/1471-2377-10-77
|View full text |Cite
|
Sign up to set email alerts
|

Combination of diffusion tensor and functional magnetic resonance imaging during recovery from the vegetative state

Abstract: BackgroundThe rate of recovery from the vegetative state (VS) is low. Currently, little is known of the mechanisms and cerebral changes that accompany those relatively rare cases of good recovery. Here, we combined functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) to study the evolution of one VS patient at one month post-ictus and again twelve months later when he had recovered consciousness.MethodsfMRI was used to investigate cortical responses to passive language stimulation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 57 publications
2
43
0
1
Order By: Relevance
“…A comparable pattern of functional impairment in the default network concomitant to a relative preservation of the white matter, has been previously reported for a UWS/VS patient who, afterward, regained consciousness (Fernández-Espejo et al, 2011). Similarly, Newcombe et al (2010) have shown that DTI-MRI may help to characterize differences in UWS/VS patients of different etiologies and Fernández-Espejo et al (2010), using a similar approach albeit restricted to mean diffusivity indices from specific regions of interest have demonstrated differences between UWS/VS and MCS patients.…”
Section: Discussionsupporting
confidence: 66%
“…A comparable pattern of functional impairment in the default network concomitant to a relative preservation of the white matter, has been previously reported for a UWS/VS patient who, afterward, regained consciousness (Fernández-Espejo et al, 2011). Similarly, Newcombe et al (2010) have shown that DTI-MRI may help to characterize differences in UWS/VS patients of different etiologies and Fernández-Espejo et al (2010), using a similar approach albeit restricted to mean diffusivity indices from specific regions of interest have demonstrated differences between UWS/VS and MCS patients.…”
Section: Discussionsupporting
confidence: 66%
“…Since introduction of DTI, many studies have demonstrated the clinical usefulness of DTI by estimating some areas of the lower portion of the ARAS from pontine RF to thalamus in patients with impaired consciousness [8,9,15,18,[22][23][24]. In addition, several studies have reconstructed some portions of the ARAS three-dimensionally: the RF -the thalamus -the cerebral cortex [6,7,10,11,27].…”
Section: Discussionmentioning
confidence: 98%
“…While the results of the patients differ from those of the control group for the reversenarrative condition, the results are still suggestive that the patients are processing speech signal as distinct from acoustically identical non-linguistic sound. Fernández-Espejo et al (2008) used a similar paradigm in a group of 3 VS and 3 MCS patients compared to 19 healthy controls, and subsequently in another single VS patient (Fernández-Espejo et al, 2010). The results suggested that there is not a clear distinction between VS and MCS patients in terms of fMRI markers of speech recognition.…”
Section: Speech and Language Processingmentioning
confidence: 99%